PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN SIGI - Abidin, Fahrud (Katalogis, 2015)
This study aims at identifying and analyzing the effect of motivation on employees performance at Department of Communication and Information of District Sigi. This is a quantitative research. The population of this research was employees of department of Transportation, Communication and Information of District Sigi which were 46 persons in total and were determined using census techniques. Data collection method consists of observation, questionnaires and documentation, while the data analysis technique used is simple linear regression analysis technique. The result indicates that there is an effect of motivation on employees performance at Department of Transportation, Communication and Information            of District Sigi, where the highest motivation dimensions is physiological needs, especially in terms of salaries received by employees in accordance with their needs, while the lowest is the dimension of self-actualization needs, which shows that the employees are lack of skills in doing their job